Propuesta de importación de la línea de bebidas gasificadas “h2oh!” a la provincia de Imbabura para la distribuidora PROVEKOM - Landeta Bolaños, Daniela Nicole (2024)
The present research is titled, proposal for the importation of the line of carbonated beverages “h2oh” to the province of Imbabura for the distributor PROVEKOM', when we talk about the market of carbonated beverages in Ecuador, we find a market too small due to the lack of variety of flavors and brands of this type of drinks, facing this lack of national supply, large supermarket chains have chosen to expand this market by bringing beverages brands recognized worldwide. The general objective of the research is to develop a proposal to import the line of carbonated beverages “h2oh” to the province of Imbabura for the distributor PROVEKOM. In order to fulfill the previous objective, information was collected through different bibliographic sources, virtual tools, such as Trade Map, Mac Map, in order to gather accurate information to develop the proposal for the importation of the product. The instruments used to obtain the results required for this project were through interviews and survey dedicated to the marketing of carbonated beverages, for which data was obtained from the company PROVEKOM, and digital media was used to obtain proformas in order to establish prices and the required variety and detail of the company, at the end of the study, the viability of the company is presented through financial data.